Policymakers' perceived barriers and facilitators in the use of research evidence in oral health policies and guidelines: a qualitative study protocol. Issue 2 (24th February 2023) - Verdugo-Paiva, Francisca; Bonfill, Xavier; Ortuño, Duniel; Glick, Michael; Carrasco-Labra, Alonso
Abstract : Introduction: Evidence-informed oral health policies are crucial to improving patient and population outcomes, but policymakers and organisational leaders infrequently systematically incorporate research evidence. Although there is indirect evidence regarding challenges in other healthcare sectors, the use of evidence-informed oral health policies remains unstudied in oral health. This study aims to assess policymakers' perceived needs, barriers and facilitators in using research evidence to inform policies in oral health. Methods and analysis: This is a qualitative study situated within a phenomenological paradigm. We will conduct semistructured interviews with policymakers (5–10) affiliated with key organisations conducting guidance, policy statements, guidelines or any knowledge transfer deliverables in oral health. Organisations will be sampled purposively and with no geographical restrictions. All interviews will be recorded, and an audio transcript will be generated. Subsequently, a researcher will review and validate the transcripts. Data will be analysed using thematic analysis supported by ATLAS.ti software. Ethics and dissemination: Ethical approval was not sought because the study protocol met the criteria for exemption from such review according to the Clinical Research Ethics Committee of the Hospital de la Santa Creu i Sant Pau and the Spanish legislation (Law 14/2007 of 3 July, on biomedical research). Informed consent will be obtained from all subjects involved in this study. The findings of this study will be shared with participating organisations for feedback, disseminated in conferences and published in a peer-reviewed journal adopting open science practices. Study registration: Open Science Framework (DOI:10.17605/OSF.IO/W4KG7).